A Discrete Subset of Monocyte-Derived Cells among Typical Conventional Type 2 Dendritic Cells Can Efficiently Cross-Present - Sheng, Jianpeng (2018)
Dendritic cells (DCs) and macrophages (Mϕs) share close developmental pathways and functional features, leading to blurring of the boundaries between these two cell lineages. However, a deeper understanding of DC and Mϕ ontogeny and more refined phenotypic and functional characterizations have helped to delineate pre-DC-derived conventional DCs (cDCs), including cDC1s and cDC2s, from monocyte-derived Mϕs. Here, we further refine DC/Mϕ cell classification and report that classically defined cDC2s contain a discrete population of monocyte-derived migratory antigen-presenting cells with Mϕ phenotype but functional DC features, including cross-presentation.